Analisis Perilaku Konsumsi Tablet Tambah Darah (Fe) Pada Remaja Putri Di Kabupaten Pati - Kamala, Faroidlillahi; Nisa, Alfiana Ainun; Indarjo, Sofwan (Yayasan Jompa Research and Development, 2025)
Anemia is a common health problem among adolescent girls in Indonesia. One preventative measure is the regular consumption of iron (Fe) tablets, but compliance remains low. This study aims to analyze factors associated with adherence to iron (Fe) tablet consumption among adolescent girls in Pati Regency. This study was a quantitative, observational, and analytical study with a cross-sectional design. The population was 291 female students at SMP Negeri 1 Cluwak, with a sample of 187 respondents selected using simple random sampling. The research instrument used a questionnaire, and data analysis was performed using the Chi-Square test or its alternative test with a significance level of <0.05. The results showed that knowledge factors (p<0.001; PR= 3.59; 95% CI=2.56-5.05), attitudes (p=0.001; PR= 1.52 95% CI=1.16-1.98), motivation (p<0.001; PR= 3.27; 95% CI=2.45-4.38), and support from health workers (p=0.011; PR= 1.36; 95% CI=1.08-1.71), were significantly related to compliance behavior in consuming iron (Fe) tablets. Meanwhile, support from schools, peers, family, and access to information did not show a significant relationship. It was concluded that compliance behavior of adolescent girls in consuming iron (Fe) tablets was influenced by internal factors and support from health workers. It is recommended that health workers and schools be more active in providing education and routine monitoring to improve compliance in consuming iron (Fe) tablets in adolescent girls.